Integrated simulation for improved mineral recovery processes - Izart, Caroline (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2021)
The consumption of mineral and metals is increasing as the population grows and the demand for mineral resources will remain high and evolve as society moves towards a carbon-neutral future. The increasing demand for metals, combined with the pressure from citizens and industries for more responsible production methods, creates the necessity to establish more sustainable mining and mineral processing practices. This project investigated the usefulness of modelling and simulation tools to enable sustainability improvement in industry in general and in the mining industry specifically. Simulation offers opportunities for better resource management, impact assessment, planning and personal training within an accessible software tool. Mineral processing simulation must consider the variability of properties (mineralogy, texture, grade, hardness etc.) within the plant feed in order to predict the processing recovery and grade of the final concentrate along the entire mine lifetime. The integration of geological, mineral processing and metallurgical concepts is thus a central part of the simulator. The present process models were developed in the Sim module of Outotec HSC Chemistry®10 software. Two of these models, which have passed through all modelling steps are presented in detail in this thesis. The first, focusing on a geometallurgical approach, aimed at providing a more accurate description of the grinding behaviour of the ores in a mill by considering the grinding parameter variations depending on the particle composition. This model, once programmed and integrated in the HSC Sim environment, was tested against pilot test results. The second model presented in this thesis is a dynamic mill model. It was conceived for digital twin simulators. This model was also validated against data gathered in a mineral processing plant sampling campaign. The study then describes how models are applied in simulators through two industry cases co-developed during this thesis project. The first case describes an operator training simulator designed to improve the operational skills of spodumene flotation plant staff. The second case study focuses on the development of a digital twin simulator for a gold processing plant. In this case study, the geometallurgical approach was critical to achieve comprehensive planning and optimization of the mine and processing plant operations.
APPROVED
Keywords: Mineral Processing; Geometallurgy; Simulation